A novel intervention for treating adults with ADHD using peripheral visual stimulation - Richter, Yael; Gordon, Carlos; Vainstein, Gabriel; Bublil-Mor, Carmel; Geisinger, Dario; Meital-Kfir, Noya; Elyoseph, Zohar (Frontiers in Psychiatry, 2023)
Objective Stimulation of the peripheral visual field has been previously reported as beneficial for cognitive performance in ADHD. This study assesses the safety and efficacy of a novel intervention involving peripheral visual stimuli in managing attention deficit hyperactivity disorder (ADHD). Methods One hundred and eight adults, 18–40 years old, with ADHD, were enrolled in a two-month open-label study. The intervention (i.e., Neuro-glasses) consisted of standard eyeglasses with personalized peripheral visual stimuli embedded on the lenses. Participants were assessed at baseline and at the end of the study with self-report measures of ADHD symptoms (the Adult ADHD Self-Report Scale; ASRS), and executive functions (The Behavior Rating Inventory of Executive Function Adult Version; BRIEF-A). A computerized test of continuous performance (The Conners’ Continuous Performance Test-3; CPT-3) was tested at baseline with standard eyeglasses and at the end of study using Neuro-glasses. The Clinical Global Impression-Improvement scale (CGI-I) was assessed at the intervention endpoint. Safety was monitored by documentation of adverse events. Results The efficacy analysis included 97 participants. Significant improvements were demonstrated in self-reported measures of inattentive symptoms (ASRS inattentive index; p = 0.037) and metacognitive functions concerning self-management and performance monitoring (BRIEF-A; p = 0.029). A continuous-performance test (CPT-3) indicated significant improvement in detectability (d’; p = 0.027) and reduced commission errors (p = 0.004), suggesting that the Neuro-glasses have positive effects on response inhibition. Sixty-two percent of the participants met the response criteria assessed by a clinician (CGI-I). No major adverse events were reported. Conclusion Neuro-glasses may offer a safe and effective approach to managing adult ADHD. Results encourage future controlled efficacy studies to confirm current findings in adults and possibly children with ADHD. Clinical trial registration: https://www.clinicaltrials.gov/, Identifier NCT05777785.